PENGARUH LAMA PENYINARAN TERHADAP STABILITAS WARNA RESIN KOMPOSIT NANOFILLER PADA PERENDAMAN LARUTAN TEH - Hindrya Firsta Ananda; Rima Semiarty; Deli Mona (Faculty of Dentistry Universitas Andalas, 2015)
Nanofiller has been used these years because it has smooth particles which will give good effect in esthetic. Failure or success of restoration depends on shade stability. The stability depends on adequate polymerization. Curing process is an important aspect to initiate polymerization. The aim of this study was to evaluate the differences of the shade between nanofiller composite resin irradiation with different curing time and also the effect of different curing time on shade of nanofiller resin composite immersed in tea solution. This research used 60 disks with 6 mm in diameter and 2 mm in thickness composite for 6 kind of acts. Group are cured for 20, 30, and 40 seconds that soaked in artificial saliva for 24 hours at 37oC and also in tea solution for 72 hours. The gradation of the shade were measured with spectrophotometry. The statistical analysis that used two way Anova showed that there was no significantly difference in shade of nanofiller composite resin irradiated with different curing times that soaked in tea solution (p>0,05) and there were significantly differences among irradiation in 20 seconds soaked in tea and saliva with irradiation group of 30 and 40 seconds (p<0.05).